Peran Media Sosial Dalam Membentuk Opini Publik Selama Pilkada 2024 di Kabupaten Merauke - RENWARIN, SILVESTER (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2025)
This study aims to analyze the role of social media in shaping public opinion during the regional elections in Merauke Regency. The focus of this study is how the use of social media by the KPU, candidate pairs, and the public influences voters' perceptions of regional head candidates and how these platforms are used to disseminate political information, mobilize support, and monitor the course of the regional elections. Researchers uses a qualitative method with a literature study approach. Data were collected from various sources, including news reports from local media such as Merauke.go.id and Radio Republik Indonesia, as well as scientific journals related to social media, political campaigns, and public opinion. The results of the study show that social media has a significant role in expanding the reach of campaigns and encouraging public participation, especially among young voters in Merauke Regency. Social media facilitates direct interaction between candidates and voters and allows the public to monitor the implementation of the regional elections. However, the main challenge found is the spread of hoaxes and disinformation that can negatively influence public opinion. In conclusion, social media has brought about important changes in the political process in Merauke Regency, creating a more inclusive space for political participation, although careful management of the information disseminated is still needed.